A hybrid framework for multimedia data processing in IoT-healthcare using blockchain technology - Rathee, Geetanjali; Sharma, Ashutosh; Saini, Hemraj; Kumar, Rajiv; Iqbal, Razi (Multimedia tools and applications, 2020)
Through the propagation of technology in recent years, people communicate in a range of ways via multimedia. The use of multimedia technique in healthcare system also makes it possible to store, process and transfer the patient’s data presented in variety of forms such as images, text and audio through online using various smart objects. Healthcare organizations around the world are transforming themselves into more efficient, coordinated and user-centered systems through various multimedia techniques. However, the management of huge amount data such as reports and images of every person leads to increase the human efforts and security risks. In order to overcome these issues, IoT in healthcare enhances the quality of patients care and reduce the cost by allocating the medical resources in an efficient way. However, a number of threats can occur in IoT devices initiated by various intruders. Sometimes, in order to make their personal profit, even though the medical shop or pathology labs are not of good reputation, the doctors forced the patients to do the lab tests, or buy the medicines from those organizations only. Therefore, security should be at the staple of outlook in IoT elucidations. In order to prevent these issues, Blockchain technology has been encountered as the best technique that provides the secrecy and protection of control system in real time conditions. In this manuscript, we will provide a security framework of healthcare multimedia data through blockchain technique by generating the hash of each data so that any change or alteration in data or breaching of medicines may be reflected in entire blockchain network users. The results have been analyzed against conventional approach and validated with improved simulated results that offer 86% success rate over product drop ratio, falsification attack, worm hole attack and probabilistic authentication scenarios because of Blockchain technique.